ONLINE MARKETING FOR TAKALAR POTTERY PRODUCTS: A QUALITATIVE ANALYSIS OF E-COMMERCE SUCCESS - Haeruddin Haeruddin; Ibrahim Ahmad; Hisnol Jamali; Imran Tahalua; Salmah Harun (Universitas Islam Lamongan, 2023)
The pottery products from Takalar Regency, Indonesia, are highly sought after by consumers for various reasons. The success of these products is based on several important factors. Firstly, these pottery products are appreciated for their high artistic and cultural value, reflecting the rich local heritage of traditions and culture. Furthermore, the main attraction of these pottery products lies in their uniqueness, capturing the attention of consumers seeking unique and distinct items. The quality of the raw materials and production techniques also leaves a positive impression on consumers who appreciate craftsmanship. The success of these products is also closely related to customer satisfaction, which, when met, tends to create loyal customers who promote the products. Through the use of social media and online marketing, pottery products from Takalar Regency can reach a wider audience, increase sales, and receive more positive responses.